Comparative Study of BaY0.1Ce0.9O3-δ Membrane with BaY0.1Zr0.9O3-δ Protective Layers Synthesized with Spray Pyrolysis and Magnetron Sputtering Methods. (2nd June 2015) - Maide, Martin; Korjus, Ove; Vestli, Mihkel; Romann, Tavo; Nurk, Gunnar
Abstract : Chemically stable BaY0.1 Zr0.9 O3-δ (BZY) layers were deposited onto the BaY0.1 Ce0.9 O3-δ (BCY) substrate using reactive magnetron sputtering and spray pyrolysis method. Dense supportive BCY substrates with good phase purity were made from BCY nanopowder synthesized from nitrate salt solutions using 2.4 MHz ultrasonic particle generator. Protective BZY layer deposited using magnetron sputtering method was approximately 0.7 mm thick, highly dense, with good phase purity and with no cracks. Spray pyrolyzed BZY layer was approximately 2-3 mm thick, with good phase purity and with some closed porosity. Electrochemical properties of BCY membrane with and without protective BZY layers were studied. Lowest activation energy (0.35 eV) was obtained for pure BCY membrane based system. Membranes with magnetron sputtered BZY coating have activation energy equal to 0.35 eV and 0.40 eV for spray pyrolized layer. Studied membranes were exposed to CO2 at 700 °C and found to be protective for the BCY.